Patient Safety Through Nursing Documentation: Barriers Identified by Healthcare Professionals and Students - Bjerkan, Jorunn; Valderaune, Victor; Olsen, Rose Mari (Frontiers in Computer Science, 2021)
Background: Although access to accurate patient documentation is recognized as a prerequisite for delivering of safe and continuous municipal elderly care, healthcare professionals often fail to provide comprehensive clinical information in an accurate and timely manner. The aim of this study was to understand the perceptions of healthcare professionals and healthcare students regarding existing barriers to patient safety through the performance of documentation practices. Methods: Using a qualitative, exploratory design, this study conducted six focus group interviews with nurses and social educators (n = 12) involved in primary care practice and nursing and social educator bachelor’s degree students from a University College (n = 11). Data were analyzed using qualitative content analysis. Results: Four themes emerged from the analysis, which described barriers to patient safety and quality in documentation practices: “Individual factors,” “Social factors,” “Organizational factors,” and “Technological factors.” Each theme also included several sub-themes. Conclusions: According to the findings, several barriers negatively influenced documentation practices and information exchange, which may place primary care patients in a vulnerable and exposed situation. To achieve successful documentation, increased awareness and efforts by the individual professional are necessary. However, primary care services must facilitate the achievement of these goals by providing adequate resources, clear mission statements, and understandable policies.